HERMENÊUTICAS EM CONFLITO: PERSPECTIVAS DE MIRCEA ELIADE E RUDOLF BULTMANN SOBRE O MITO - ALMEIDA, SÉRGIO CESAR PRATES DE (2017)
The objective of this research is to address the distances that exist on Mircea Eliade and Rudolf Bultmann’s perspectives about the myth. As we investigate the issue of myth and its interpretations we find that there are many significant discussions about the theme. Among them, unquestionably, two stand out not because of their role over others, but because of the importance that this question plays in the thinking of their researchers, since it is practically impossible to disassociate the question from the myth on Mircea Eliade and Rudolf Bultmann’s thoughts. For Eliade the myth reveals that the world, human and life have a supernatural origin and story. This sacred story, besides being true, is significant, precious and exemplary, as it makes reference and brings meaning to the realities of a certain society to which the myth belongs. In contrast Bultmann notes a problem to be solved in the application of his hermeneutics: how to relate to the question of the myth present in the New Testament writings. The myth is a threat to the modern mind steeped in a scientific worldview. Myth and modern thought are totally excluding. What Bultmann insists on is the elimination of the conceptual universe of the New Testament so that the word of God can be understood by modern man. The myth, therefore, in Bultmann's conception is nothing more than a way of objectifying what is transcendent to the immanent, is to transform divine beings into humans. In this way, we will analyze the assumptions that led both to take different paths and construct opposite hermeneutics of the myth. And finally, to understand the repercussions of hermeneutical practices for contemporary religious thoughts.